Synthesis & Characteristics of PPy - MgO –CuO Nanocomposite for CO2 Gas Sensors Applications (International Journal of Scientific Research in Science and Technology, 2024)
The MgO, CuO nanoparticles was synthesized by sol-gel method, and polypyrrole(PPy) was a synthesized by chemical oxidative polymerization technique for a period of four hours (4h) at room temperature using pyrrole monomer in aqueous solution. Unlike oxidants such as ferric chloride (FeCl3) and ammonium persulphate (N2H8S2O8) were used. The sample PPy in the form of odorless black powder were prepared. The synthesized nanoparticles was characterized by powder X-Ray Diffraction (XRD), Scanning electron microscopy (SEM). The XRD studies of this sample confirmed the emergence of cubic structure and the particles size and lattice constant were analyzed. It shows that the morphology of PPy samples has a significant influence on the conductivity. The conducting polymer-polypyrrole has highly eolotropic of electrical conduction and operated as a CO2 gas sensor. The different MgO-PPy, CuO-PPy , MgO-CuO Composite by weight % were prepare by the screen-printing method on Al2O3 layer after by glass substrate. This sensors was used for dissimilar concentration (ppm) of CO2 gas study at room temperature. The structure and morphology of synthesized nanoparticles was investigated utilizing of X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM)